A CRITICAL STUDY OF ACTS 2-4 IN THE LIGHT OF KARL MARX’S “RELIGION IS THE OPIUM OF THE MASSES” - Ugochukwu, Obumneme Ezewudo; Kalu, Ngele Omaka; Uroko, Favour Chukwuemeka (QUAERENS: Journal of Theology and Christianity Studies, 2024)
Karl Marx’s analysis and critique of religion captured in his statement: Religion is the opium of the masses is perhaps one of the most famous and most quoted by theists and atheists. Unfortunately, most of those doing the quoting do not really understand exactly what Marx meant, probably due to an incomplete understanding of Marx’s general theories on economics and society. Marx’s theory on religion as the opium of the masses is based on his belief that religion had certain practical functions both positive and negative to perform in the society. Such practical functions are seen and observed in the contemporary world. His theory was critically examined in the light of Acts 2-4 in order to discover its effect and implications for church and society using economic strait. The methodology adopted is historical critical method and redaction criticism in biblical scholarship. However, many factors are considered responsible for oppression and social disorder. In agreement with some aspects of Marx’s view on religion, this paper observes and recommends need for psychological emancipation from religious dogmatism.